Recruitment and Patch Establishment by Seed in the Seagrass Posidonia oceanica: Importance and Conservation Implications - Balestri, Elena; Vallerini, Flavia; Lardicci, Claudio (Frontiers in Plant Science, 2017)
Seagrasses are declining globally, and deeper understanding is needed on the recruitment potential and distribution of new populations for many threatened species to support conservation planning in the face of climate change. Recruitment of Posidonia oceanica, a threatened seagrass endemic to the Mediterranean, has long been considered rare due to infrequent flowering, but mounting evidence demonstrates that the species is responding to a changing climate through greater reproductive effort. Due to the fragmentary information on recruit occurrence and distribution, little is known about reproductive success in the species and its contribution to persistence. We assembled P. oceanica recruitment data from published and unpublished sources, including our own, to examine the frequency and extent of recruitment events (establishment of seedlings in a site), seedling growth potential and habitat characteristics at recruitment sites. Results show that at least one recruitment event has occurred about every three years, and eighteen localities were colonized at least one time since the first seedling record in 1986. Notably, consistently high seedling inputs were observed in four localities of the Western Mediterranean. Seedlings established mainly on unoccupied substrate areas along the coasts of islands, in sheltered sites and at shallower depths (<3 m) than the upper limit of adjacent P. oceanica meadows. Seedling establishment occurred more frequently on rocky than on sandy substrate, and rarely on dead “matte” or meadows of the seagrass Cymodocea nodosa. The chance of colonization success on rock was two times higher than on sand. Our 11 years of observations have allowed for the first time the documentation of the formation and development of patches by P. oceanica seed. These findings contradict the historical assumption that sexual recruitment is rare and usually unsuccessful for P. oceanica, and highlight the potential importance of recruitment for the long-term persistence and adaptation of the species to sea level rise predicted in the next century in the Mediterranean. Unfortunately, management actions have mainly focused on established meadows, ignoring the presence of recruits in outside areas. Therefore, it will be useful to identify and consider regeneration sites in designing future management strategies to improve seagrass conservation effectiveness.